Sewa Menyewa Kendaraan Bermotor Yang Masih Menjadi Objek Jaminan Fidusia - Pattiikawa, Janles Piero; Akyuwen, Rory Jeff; Kuahaty, Sarah Selfina (Faculty of Law Universitas Pattimura, 2025)
This article explains about motor vehicle guarantee agreement or fiduciary guarantee agreement regulated in the articles and laws applicable in cases leading to fiduciary guarantee agreement. The purpose of this article is to find out and explain what the legal consequences are in renting a vehicle that is still the object of fiduciary guarantee, and what form of responsibility the debtor is responsible for the collateral object that is rented without notification to the creditor. The type of research used is normative juridical using two research approaches consisting of a statutory approach and a conceptual approach. The results of the study explain that the legal consequences of a motor vehicle lease agreement with the object of the vehicle being used as fiduciary guarantee without written permission that is contrary to the law, then the legal consequences of the agreement are null and void because it does not meet the objective requirements and is considered to have no legal force. Actions from the form of responsibility carried out without the consent of the creditor, then the debtor is absolutely responsible. For all losses suffered by the lessee or the creditor when the lease action causes losses.